Phosphorylation-Dependent Regulation of Mammalian Aquaporins - Nesverova, Veronika (Cells, 2019)
Water homeostasis is fundamental for cell survival. Transport of water across cellular membranes is governed by aquaporins—tetrameric integral membrane channels that are highly conserved throughout the prokaryotic and eukaryotic kingdoms. In eukaryotes, specific regulation of these channels is required and is most commonly carried out by shuttling the protein between cellular compartments (trafficking) or by opening and closing the channel (gating). Structural and functional studies have revealed phosphorylation as a ubiquitous mechanism in aquaporin regulation by both regulatory processes. In this review we summarize what is currently known about the phosphorylation-dependent regulation of mammalian aquaporins. Focusing on the water-specific aquaporins (AQP0–AQP5), we discuss how gating and trafficking are controlled by phosphorylation and how phosphorylation affects the binding of aquaporins to regulatory proteins, thereby highlighting structural details and dissecting the contribution of individual phosphorylated residues when possible. Our aim is to provide an overview of the mechanisms behind how aquaporin phosphorylation controls cellular water balance and to identify key areas where further studies are needed.